INFORMATION SOURCES OF ECONOMIC COMPETENCE ANALYSIS OF ECONOMIC SUBJECTS AND THEIR CLASSIFICATION (American Journal of Business Management, Economics and Banking, 2025)
In this article, the importance of information sources in the analysis of the economic potential of economic entities and ensuring the reliability of the information used in the analysis process, taking into account the interests of owners, management bodies, investors and other interested parties, classifying economic potential information sources and improving the methodological aspects of forming their system of private and general indicators, issues of improving economic potential management methods aimed at improving investment attractiveness, taking into account the characteristics of the national economy, and ensuring stable and proportionate economic growth in our country, increasing the effectiveness of economic reforms, identifying new growth points based on an in-depth analysis of the current state of socio-economic development of the regions, and using the existing economic potential sufficiently special attention is paid to use. In particular, the effectiveness and efficiency of modern management processes directly depends on their timely provision with reliable, scientifically based and analytical information. Also, today there are so many issues, objects of management and factors affecting the result that are studied in the process of management, that as a result, the study of each process, activity or object separately shows its influence on the final result.